2020
DOI: 10.1210/jendso/bvaa111
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Resistance in Premature Adrenarche and PCOS: From Childhood to Adulthood

Abstract: Context We hypothesize that impaired glucocorticoid sensitivity (GC Sensitivity) plays a role in the development of Premature Adrenarche (PA) and polycystic ovarian syndrome (PCOS) by increasing androgen synthesis. Objective To study glucocorticoid sensitivity in vitro in subjects with Premature Adrenarche and PCOS. Patients and Methods 14 subjects (10 girls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In summary, we conclude that this novel F-Dex binding assay is accurate and reproducible as shown in our paper [ 4 ]. We conclude that in patients with premature adrenarche and PCOS, the F-Dex binding assay can be used as an additional tool in the more detailed characterization of this patients.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…In summary, we conclude that this novel F-Dex binding assay is accurate and reproducible as shown in our paper [ 4 ]. We conclude that in patients with premature adrenarche and PCOS, the F-Dex binding assay can be used as an additional tool in the more detailed characterization of this patients.…”
supporting
confidence: 73%
“…Hence, we were able to identify patients with alterations in GC sensitivity. This in vitro assay has demonstrated that GC resistance exists in the subgroup of patients as described in our study and etiology of this resistance can be heterogenous [ 4 ].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…PCOS also appears to be connected to impaired GC signaling. GC resistance was found in almost 67% of patients with PCOS in the study by Panayiotopoulos et al (80). Corticosteroids have also been used in the treatment of certain cancer types, such as hemangiomas, taking advantage of their ability to inhibit angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of Panayiotopoulos et al that glucocorticoid resistance (GR) accounted for 57% to 67% of their premature adrenarche and polycystic ovary syndrome (PCOS) cases [ 1 ] cannot be accepted from the data presented. This is because proper validation of their method for determining glucocorticoid sensitivity is not presented.…”
mentioning
confidence: 99%